The effectiveness of childbirth education in reducing pre-labor anxiety among primigravida mothers - Suci Qardhawijayanti; Asmah Sukarta; Selviana Rahayu (THE JOURNAL OF Mother and Child Health Concerns, 2026)
Background: Childbirth is defined as the process of the expulsion of a full-term fetus, initiated by regular uterine contractions and ending with the delivery of the baby, followed by the expulsion of the placenta and fetal membranes. Childbirth is one of the events most likely to provoke fear and anxiety in pregnant women, particularly among primigravida mothers. Purpose: to determine and analyze the effectiveness of childbirth education in reducing pre-labor anxiety among primigravida mothers. Method: This study employed a pre-experimental design using a quantitative approach. The sampling technique applied was total sampling. The sample consisted of 35 primigravida mothers, and data were collected using the Pregnancy-Related Anxiety Questionnaire–Revised 2 (PRAQ-R2). Results: The results of this study, based on the Wilcoxon signed-rank test, showed that the significance value before and after childbirth education was 0.001, which is less than 0.05. This indicates a statistically significant difference in anxiety levels before and after the provision of childbirth education. Conclusion: In conclusion, there was a significant difference in the anxiety levels of primigravida mothers before and after receiving childbirth education. Therefore, childbirth education can help reduce anxiety prior to labor.